Novel Phaeoacremonium species associated with necrotic wood of Prunus trees - Damm, U. (Nationaal Herbarium Nederland & Centraallbureau voor Schimmelcultures, 2008)
The genus Phaeoacremonium is associated with opportunistic human infections, as well as stunted growth and die-back of various woody hosts, especially grapevines. In this study, Phaeoacremonium species were isolated from necrotic woody tissue of Prunus spp. (plum, peach, nectarine and apricot) from different stone fruit growing areas in South Africa. Morphological and cultural characteristics as well as DNA sequence data (5.8S rDNA, ITS1, ITS2, β-tubulin, actin and 18S rDNA) were used to identify known, and describe novel species. From the total number of wood samples collected (257), 42 Phaeoacremonium isolates were obtained, from which 14 species were identified. Phaeoacremonium scolyti was most frequently isolated, and present on all Prunus species sampled, followed by Togninia minima (anamorph: Pm. aleophilum) and Pm. australiense. Almost all taxa isolated represent new records on Prunus. Furthermore, Pm. australiense, Pm. iranianum, T. fraxinopennsylvanica and Pm. griseorubrum represent new records for South Africa, while Pm. griseorubrum, hitherto only known from humans, is newly reported from a plant host. Five species are newly described, two of which produce a Togninia sexual state. Togninia africana, T. griseo-olivacea and Pm. pallidum are newly described from Prunus armeniaca, while Pm. prunicolum and Pm. fuscum are described from Prunus salicina.